(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Setyowati EA, Santoso S, Rokhmani, Rochmatino. 2022. Diversity and prevalence of endoparasites in domestic chickens across an elevation gradient. Biodiversitas 23: 3936-3942. The domestic chicken farm is negatively affected by endoparasites, which decrease immunity, egg production, and body weight. Although these effects are well understood in large-scale chicken farms, here we aimed to understand endoparasite diversity and prevalence in the context of local-scale domestic chicken farms conducted in Central Java, Indonesia, according to elevation. Chickens were sampled from three villages each in two regions; lowland in Banyumas District and highland in Purbalingga. The result showed that the diversity of endoparasite is very low (H’ index: 1.3065-1.3773) and we detected only four endoparasite species (Ascaridia galli, Trichuris trichiura, Heterakis gallinarum (Nematoda), and Raillietina sp. (Cestoda) among a sample of 300 chickens. Endoparasite infection was significantly more prevalent in the lowland villages (70%) than in highland (48%,) (p < 0.05). Among endoparasites found, A. galli was the most prevalent species among all samples (50.0±0.0% of infections in the lowlands and 23.7±1.15% in the highlands) the second is H. gallinarum accounted for 38.3±7.64% of all infections in the highlands and 15.3±0.58% in the lowlands. Raillietina sp. accounted for 35.0±5.0% and 7.3±0.58% of all infections, and T. trichiura accounted for 25.0±5.0 % and 16.0±1.0%. The rate of endoparasite infection within the study area is currently moderate and mainly affected by methods of farm, our findings can serve as a baseline for controlling infection in domestic chickens.